Rehabilitation of teenagers of patients by a cerebral paralysis by facilities of physical culture - Vindiuk P.A (Kharkov National Pedagogical University, 2012)
Influence of physical exercises is investigated in combination with mobile games on power supply of organism of teenagers of patients by a cerebral paralysis. In research took part 16 schoolchildren of teens with the spastic cerebral paralysis. For determination of their functional preparedness multivariable express diagnostics of S.A. Dushanin was utillized. It is recommended in the lessons of physical culture to include the specially organized mobile games, elements of cross-country race preparation and employment on exercise bicycle. It is set that an early and successive rehabilitation and physical education is instrumental in maximally complete renewal of the lost functions. It is marked that the index of maximal consumption of oxygen was increased on 7,4%, to the aerobic economy - on 3,1%. It is set that the lessons of physical culture in growth of indexes of functional preparation were instrumental.